Dissolving Microneedles for Transdermal Drug Delivery System. (October 2020) - Bai, Chenlin; Huo, Cheng; Zhang, Peiyu
Abstract: There is a remarkable interest in research on dissolving micromachined needles or dissolving microneedle (DM) for transdermal drug delivery (TDD) because the devices with DMs can deliver drugs without leaving potentially dangerous residues of sharps waste after use. DMs encapsulated medications into microneedles built by water-soluble materials. Both drugs and microneedles can dissolve into the human tissues after the needles insert the skin. This paper reviewed the DM technology, including the materials and pathway for TDD, manufacturing techniques, and facing challenges. The materials and the pathways for TDD are described. Micromachining technology has been employed to manufacture dissolving microneedles including micromolding, lithography, and the droplet-born air blowing. Moreover, their challenges are discussed as well. Finally, the development of DMs has been also prospected.